Pemupukan Berimbang Spesifik Lokasi Melalui Evaluasi Kesuburan Tanah di Lahan Sawah Kecamatan Klungkung Provinsi Bali - DEWA AYU PUTU SRI WAHYUNI; I DEWA MADE ARTHAGAMA; NI MADE TRIGUNASIH (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2023)
Location Specific Balanced Fertilization Through Evaluation of Soil Fertility Status in Rice Field, Klungkung District, Bali Province Rice is the main commodity cultivated by farmers in Indonesia, but there are obstacles in the productivity of rice plants, one of which is fertilization. Location-specific balanced fertilization is carried out to determine the application of fertilizer according to the fertility status of paddy fields so that fertilization will be more efficient. This study aims to determine soil fertility status, spatial distribution of soil fertility status, and provide site-specific balanced fertilization recommendations for paddy fields in Klungkung Sub-district area. This research using survey methods and soil tests in the laboratory and integrated using Geographic Information System (GIS). This research was initiated by spatial analyst for mapping the Land Unit (SLH) area with overlaid the thematic maps (i.e., soil types, slope, and paddy field area). Then four land unit maps were obtained, and soil samples were taken by purposive sampling and the chemical properties of the soil were analyzed including: CEC; KB; C-organic; P-total; and K-total. The results showed that the soil at the study site had three soil fertility statuses, namely low fertility status located at SLH II (Tangkas Village) with an area of 37.53 ha and SLH III (Selat Village) with an area of 46.26 ha, medium fertility status located at SLH IV (Akah Village) with an area of 36.31 ha, while high soil fertility status is located in SLH I (Jumpai Village) with an area of 96.53 ha. Parameters of low P-total and total K content in SLH II (Tangkas Village) and SLH III (Selat Village) became a limiting factor in soil fertility status, so it was necessary to add 100 kg/ha of SP-36 fertilizer, Phonska 100 NPK fertilizer kg/ha, and the addition of KCl fertilizer as much as 100 kg/ha.